Kinetics, isotherms, and thermodynamic studies on the adsorption of mercury (ii) ion from aqueous solution using modified palm oil fuel ash - Imla Syafiqah, Mohd Salleh; Wan Mohd Hafizuddin, Wan Yussof (Elsevier Ltd, 2018)
Palm oil fuel ash (POFA) is a waste material generated from the boiler due to the burning of palm oil biomass e.g. kernel shell and fiber as fuel to generate electricity. The present research focused on the study of adsorption isotherms, kinetics and thermodynamic properties on the removal of mercury (II) ion onto POFA. The prepared POFA was characterized by FTIR, TGA and BET analysis. The equilibrium data at various concentrations were analyzed by Langmuir and Freundlich isotherms models. From this present study, the maximum adsorption capacity obtained from the Freundlich isotherm was 0.99 mg/g. A kinetic study was carried out with pseudo first order and pseudo second order reaction equations. It was found that the mercury (II) ion uptake process followed the pseudo second order rate expression. Thermodynamic parameters of the Gibbs free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°) were also determined. The negative Gibbs free energy change (-788.90 kJ/mol) and the positive enthalpy change (73,680.33 kJ/mol) indicated that adsorption was spontaneous process and endothermic nature. Overall, POFA looks to be a promising adsorbent for removal of mercury (II) ion from aqueous solutions due to its high performance and availability at low cost.